Effects of Iron and Vitamin C on Growth Performance, Iron Utilization, Antioxidant Capacity, Nonspecific Immunity, and Disease Resistance to Aeromonas hydrophila in Chinese Mitten Crab (Eriocheir sinensis) - Ying Song; Xinyu Cai; Xianyong Bu; Shubin Liu; Mingqi Song; Yiwen Yang; Xiaodan Wang; Qingchao Shi; Jianguang Qin; Liqiao Chen (Aquaculture Nutrition)
Iron is an essential trace element with an abroad physiological function, and iron deficiency can impair animal health. Vitamin C (VC) has the potential to release iron from diets and increase iron uptake. This study evaluates the effects of dietary iron and vitamin C on the growth performance, iron utilization, antioxidant capacity, and nonspecific immunity of the Chinese mitten crab (Eriocheir sinensis). Juvenile E. sinensis (1.14±0.01 g) were fed six diets supplemented with three levels of iron (41.40, 92.25, and 143.00 mg/kg), and each iron level supplemented either 4.33 mg/kg or 700.90 mg/kg of vitamin C for 8 weeks. Crabs fed 41.40 mg/kg of iron diet had the lowest weight gain (WG) and specific growth rate (SGR) and had the highest feed conversion rate (FCR) regardless of dietary vitamin C levels. Dietary 700.90 mg/kg of vitamin C improved WG and SGR but decreased FCR when the diets were supplemented with 41.40 and 143.00 mg/kg of iron (P<0.05). Dietary 700.90 mg/kg of vitamin C significantly improved the expression levels of divalent metal ion transporter 1, ferroportin, and iron regulation protein in the intestine and hepatopancreas when supplemented with 92.25 and 143.00 mg/kg of iron (P<0.05) and enhanced the transferrin content in hemolymph and iron deposition in the hepatopancreas when supplemented with 92.25 and 143.00 mg/kg of iron (P<0.05). Crabs fed the diet supplemented with 41.40 mg/kg of iron had the highest malondialdehyde content and the lowest superoxide dismutase activity in the hepatopancreas. Dietary 700.90 mg/kg of vitamin C supplementation also increased the acid phosphatase and bacteriolytic activity when diets were supplemented with 41.40 and 143.00 mg/kg of iron (P<0.05). In addition, crabs fed 143.00 mg/kg of iron and 700.90 mg/kg of vitamin C diet had the highest survival rate after the Aeromonas hydrophila challenge. This study demonstrates that dietary 700.90 mg/kg of vitamin C could promote iron absorption and utilization, thereby increasing the growth, immunity, and disease resistance of E. sinensis.